Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Driver GO-JEK di Kota Denpasar, Bali - Giri, Putu Citrayani; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 6, Juni 2017 (pp. 920 - 1156), 2017)
The development of driver online had increased in Bali especially GO-JEK. It make competition between driver online, that affects to income of GO-JEK’s driver. The purpose of this study are to analyze 1) the influence time works, age, the level of education and work experiences simultaneously against revenue of GO-JEK’s driver, 2) the influence time works, age, the level of education and work experiences in partial against revenue GO-JEK’s driver. This research do in the Denpasar City, Bali. This study used simple random sampling methods. The collection of data in this research is using questionnaires, interviews, and observation method. This study is using multiple linear regression technique. The results of this study are data analysis found that time works, age, the level of education, and work experiences influential simultaneously against revenue GO-JEK.’s driver. Variable of working hours and work experiences have a positive and significant influence, but age and education level variable not affected to income of GO-JEK’s driver.
Keywords: jam kerja; tingkat pendidikan; umur; pengalaman kerja; pendapatan